The Role of BPD in Preparation of APBD to Realize Village Autonomy - Muhammad Ali Maskun; Siti Rodhiyah Dwi Istinah (Law Development Journal, 2021)
Destination from this research, namely: To know and analyze the procedures for the preparation of the Village Budget (APBD) in the framework of realizing village autonomy. To find out and analyze the role of the Village Consultative Body (BPD) in Budget Formulationm Village Income and Expenditure (APBD) to realize village autonomy. To find out and analyze obstacles and solutions to the role of the Village Consultative Body (BPD) in the Preparation of the Village Revenue and Expenditure Budget (APBD) to realize village autonomy. The method used by researchers is juridical sociological approach to law and the specifications in this research are descriptive. Based on the results of that research The Village Income and Expenditure Budget (APBD) Preparation Procedure in the framework of realizing village autonomy is as follows: The activity implementer submits activity budget proposals to the village secretary based on the stipulated RKP’s village; The Village Secretary prepares the Draft Village Regulation on APB’s village (RAPB’s village) and submits it to the Village Head. The role of the Village Consultative Body (BPD) in the Preparation of the Village Revenue and Expenditure Budget (APBD) to realize village autonomy, among others, is to convey the idea of managing village funds as a form of collecting community aspirations as determining priorities for implementing village fund management with consideration of the village head. The process of planning the Village Fund Budget management during village meetings, low community self-help, delays in disbursement of village funds, changes in nominal APB’s village funds received and a new Regent regulation. Efforts to overcome this problem include the Blerong village government with an agreement with the Village Consultative Body to disseminate information on the importance of community self-help, then use Village Original Income funds, and Fund Less Channels, whose implementation is in accordance with the provisions of the applicable legislation.